The Relationship Between Employer Branding, WOM, and Fresh Graduates’ Intention to Apply Job in SMEs - Aun, Tan Lok; Kamalul Ariffin, Shaizatulaqma (Journal of Entrepreneurship, Business and Economics, 2026)
This conceptual paper explains fresh graduates’ intention to apply job in SMEs under information asymmetry using a signalling-based framework. Five employer-branding values: economic, development, application, interest, and social to operate as deliberate signals that applicants integrate into a higher-order corporate reputation, which in turn drives the intention to apply. We argue that word-of-mouth (WOM) strengthens the Reputation-Intention linkage by adding socially verified credibility at the point of action. Synthesising evidence with the Malaysian SME context, we develop seven propositions that specify a signal–inference–intention mechanism. We further discuss the relative salience among the five values and propose a measurement blueprint for future empirical tests. The paper contributes by clarifying construct roles values shape reputation, and reputation shapes intention to apply job, elevating WOM to a contextual moderator, and translating these mechanisms into actionable guidance for resource-constrained SMEs. We conclude by articulating a theoretically grounded, context-aware roadmap to help Malaysian SMEs compete more effectively for fresh graduates. Conceptual Paper Keywords: Employer branding; Corporate reputation; Word-of-mouth; Fresh graduates; Intention to apply job Reference to this paper should be made as follows: Aun, T.L., & Kamalul Ariffin, S. (2025). The Relationship Between Employer Branding, WOM, and Fresh Graduates’ Intention to Apply Job in SMEs. Journal of Entrepreneurship, Business and Economics , 13 (2), 154–187.